Evaluating farmland ecosystem resilience and its obstacle factors in Ethiopia. (February 2023) - Yang, Shengjie; Song, Shuai; Li, Fadong; Yu, Guangming; He, Guizhen; Cui, Haotian; Wang, Rui; Sun, Bin; Du, Di; Chen, Gang; Hirwa, Hubert
Graphical abstract: Highlights: A conceptual model for farmland ecosystem resilience (FER) assessment was developed. Disturbance-response processes and self-regulation mechanism of FER were revealed. The sustainability of Ethiopia's farmland ecosystems has generally improved. The antagonism and synergy between the response factors appeared more significant. Abstract: In the context of global warming, the sustainability of farmland ecosystems is increasingly impacted by multiple disturbances from both natural and human-induced sources. This study constructed a conceptual model and indicator system of farmland ecosystem resilience (FER) based on the disturbance-response processes of farmland ecosystems. FER assessment, supported by 30 specific indicators, was tested in Ethiopia, one of the most food-insecure countries in the world and the factors impending farmland ecosystem sustainability were discussed based on the obstacle degree values (ODVs). The results showed that the FER change rate in Ethiopia was 0.3 %/year during 2003–2018, indicating positive sustainability on the whole. However, in the five years of 2004, 2007, 2008, 2011, and 2017, the FER decreased, among which the largest decline was −0.017 in 2017. Natural comprehensive disturbance (ND), human activity disturbance (HD), resilience of farmland supply (RFS), and resilience of social support (RS) were the key constraints of FER, while the ODVs of ND and RFS showed increasing trends. We also found that there were general antagonistic and synergistic effects among the response factors and the synergistic enhancement between disturbance factors was more pronounced than the antagonistic buffering effect. This study provides a fresh perspective for farmland ecosystem managers and stakeholders to examine disturbance risks and assess the sustainability of farmland ecosystems.